CITRA TUBUH PEREMPUAN YANG MELAKUKAN BEDAH KOSMETIK - , Theresia Epifanie; , Dr. Ira Paramastri, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Behavior of cosmetic surgery being performed by the third subject in this study is based on the views on the ideal body. Description of the ideal that is owned by the subject apparently does not correspond to the physical reality. Although the overall subject of third states are happy with their physical appearance, there are some body parts that create discomfort. Two people the subject stated that the wattle stomach after birth raises uncomfortable feelings in the activity. One subject ever wound up injecting silicone in the lips and nose. The perceived inconvenience of the trio, supported by easily obtained information about cosmetic surgery, as well as support from the people around them. The results of this research gave rise to a third subject that has a view about the proportions and form in terms of the ideal body, the reality of physical appearance that gave rise to certain feelings about the body, the information obtained relating to problems faced then gave rise to the desire and the decision to perform cosmetic surgery. Response that leveled up cosmetic surgery done turns out to have a difference, two persons subject expressed delight with the results of cosmetic surgery has been done, while one person the subject feel hasn't gotten an ideal form after doing cosmetic surgery. The dynamics of body image and cosmetic surgery experienced by the subject's perception regarding the appearance of the enshrined, developments, sociocultural, and self esteem.